Early postnatal care use by postpartum mothers in Mundri East County, South Sudan - Jonathan Izudi; Grace Denise Akwang; Dinah Amongin (BMC, 2017)
Abstract Background Globally, most maternal and newborn deaths are within the first week of delivery. Early postnatal-care (EPNC) visits between 2 and 7 days detects early morbidity and averts deaths. However, there is scarcity of information on use of EPNC in Mundri East County, South Sudan. This study investigated factors associated with EPNC use among postpartum mothers in Mundri East County, South Sudan. Methods This was an analytical cross-sectional study of 385 postpartum mothers from 13 health facilities. Data was collected by structured questionnaires, entered in EpiData and analyzed with STATA at 5% significance level. Chi-squared, Fisher's exact and Student's t-tests were used for bivariate analysis and logistic regression for multivariable analysis. Results The mean age of respondents was 27.9-years (standard deviation: 6.7), 276 (71.7%) were below 30-years, 163 (42.3%) were Muru ethnicity, 340 (88.3%) were single and 331 (86.1%) were unemployed. 44 (11.4%; 95% CI: 8.4-15.0) used EPNC. Poor health services access at government health facilities (Adjusted odds ratio (AOR) = 0.18; 95% CI: 0.05-0.61; P = 0.006), more than 1-h access to health facility (AOR = 0.27; 95% CI: 0.09-0.78; P = 0.015), at least secondary maternal education (AOR = 5.73; 95% CI: 1.14-28.74; P = 0.034) and receipt of PNC health education post-delivery (AOR = 3.47; 95% CI: 1.06-11.33; P = 0.004) were associated with EPNC use. Conclusions Use of EPNC in Mundri East County, South Sudan was low. It was significantly reduced at government and inaccessible health facilities. However, it increased with receipt of PNC health education after delivery and at least secondary level of education.